2013
DOI: 10.1056/nejmoa1207564
|View full text |Cite
|
Sign up to set email alerts
|

Four-Year Efficacy of RTS,S/AS01E and Its Interaction with Malaria Exposure

Abstract: The efficacy of RTS,S/AS01E vaccine over the 4-year period was 16.8%. Efficacy declined over time and with increasing malaria exposure. (Funded by the PATH Malaria Vaccine Initiative and Wellcome Trust; ClinicalTrials.gov number, NCT00872963.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
221
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(228 citation statements)
references
References 16 publications
3
221
1
3
Order By: Relevance
“…Similarly, the seroprevalence of antibodies to 39 P. falciparum antigens, including vaccine targets, varied in a Kenyan cohort, with most (96%) glycophophatidylinositol (GPI)‐anchored antigens being detected, whereas rhoptry‐associated proteins, which are mostly conserved antigens, were sparingly (5%) detected 73. Clinical trials of RTS,S, a malaria vaccine which targets the pre‐erythrocytic stage, have also demonstrated that vaccine recipients had higher antibody titres relative to non‐vaccinated individuals; however, protection was observed in < 40% of vaccine recipients and protection waned with time 24. The recently characterized P. falciparum sporozoite‐based malaria vaccine (PfSPZ) might provide a glimmer of hope, but similar to the pattern observed for the RTS,S vaccine, protection was also observed in 64% of vaccine recipients in a controlled human malaria infection and, particularly, antibody levels did not segregate protected from non‐protected individuals 20, 74, 75…”
Section: Antibodies and Protection: What We Have Learnt So Farmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the seroprevalence of antibodies to 39 P. falciparum antigens, including vaccine targets, varied in a Kenyan cohort, with most (96%) glycophophatidylinositol (GPI)‐anchored antigens being detected, whereas rhoptry‐associated proteins, which are mostly conserved antigens, were sparingly (5%) detected 73. Clinical trials of RTS,S, a malaria vaccine which targets the pre‐erythrocytic stage, have also demonstrated that vaccine recipients had higher antibody titres relative to non‐vaccinated individuals; however, protection was observed in < 40% of vaccine recipients and protection waned with time 24. The recently characterized P. falciparum sporozoite‐based malaria vaccine (PfSPZ) might provide a glimmer of hope, but similar to the pattern observed for the RTS,S vaccine, protection was also observed in 64% of vaccine recipients in a controlled human malaria infection and, particularly, antibody levels did not segregate protected from non‐protected individuals 20, 74, 75…”
Section: Antibodies and Protection: What We Have Learnt So Farmentioning
confidence: 99%
“…So far, tremendous progress has been made, and several targets have been identified as vaccine candidates. In fact, a vaccine based on a liver stage antigen, the circumsporoite protein (CSP), has made it all the way to licensure (RTS,S vaccine),16, 17, 18, 19 while a handful of other antigens have been characterized and are in phases II and III clinical trials 20, 21, 22, 23, 24…”
Section: Introductionmentioning
confidence: 99%
“…This arose because of antigenic polymorphism and poor immunogenicity of subunit vaccine candidates. Even the recently licensed vaccine, RTS,S, can provide only modest and short‐term protection,1, 2, 3 which correlates with a lack of antigenic boosting following sporozoite exposure and antigenic polymorphism of the vaccine 4. In 2011 and 2013, the first clinical trials of a whole‐parasite malaria sporozoite vaccine were reported 5, 6.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are great challenges in developing a highly effective malaria vaccine, progress has accelerated considerably in last decade with ∼25 vaccine candidates at different stages of development (3). Farthest along is the preerythrocytic RTS,S vaccine, shown in recent phase III clinical tries to be between 25% and 50% effective against the disease (4,5) and receiving a World Health Organization (WHO) recommendation to begin its use in 2015 provided it gains approval. Other candidates are also showing increased promise (6,7).…”
mentioning
confidence: 99%
“…The leading vaccine candidates currently in development can be classified into three general families (Fig. 1A): (i) preerythrocytic vaccines (PEVs), such as the RTS,S (4,5), which reduce the chances of a person becoming infected, (ii) blood-stage vaccines (BSVs), which reduce the level of disease severity and fatality, and (iii), transmission-blocking vaccines (TBVs), which target the sexual stages of the parasite and disrupt the malaria transmission cycle. In contrast to the first two, the TBV provides very limited benefit to the people vaccinated but potentially reduces the rate at which they infect others; for this reason it is commonly referred to as an altruistic vaccine (28)(29)(30).…”
mentioning
confidence: 99%